C1Q Assay Results in Complement-Dependent Cytotoxicity Crossmatch Negative Renal Transplant Candidates with Donor-Specific Antibodies: High Specificity but Low Sensitivity When Predicting Flow Crossmatch - José M. Arreola-Guerra; Natalia Castelán; Adrián de Santiago; Adriana Arvizu; Norma Gonzalez-Tableros; Mayra López; Isaac Salcedo; Mario Vilatobá; Julio Granados; Luis E. Morales-Buenrostro; Josefina Alberú (Journal of Transplantation)
The aim of the present study was to describe the association of positive flow cross match (FXM) and C1q-SAB. Methods. In this observational, cross-sectional, and comparative study, patients included had negative AHG-CDC-XM and donor specific antibodies (DSA) and were tested with FXM. All pretransplant sera were tested with C1q-SAB assay. Results. A total of 50 donor/recipient evaluations were conducted; half of them had at least one C1q+ Ab (n=26, 52%). Ten patients (20.0%) had DSA C1q+ Ab. Twenty-five (50%) FXMs were positive. Factors associated with a positive FXM were the presence of C1q+ Ab (DSA C1q+ Ab: OR 27, 2.80–259.56, P=0.004, and no DSA C1q+ Ab: OR 5, 1.27–19.68, P=0.021) and the DSA LABScreen-SAB MFI (OR 1.26, 95% CI 1.06–1.49, P=0.007). The cutoff point of immunodominant LABScreen SAB DSA-MFI with the greatest sensitivity and specificity to predict FXM was 2,300 (sensitivity: 72% and specificity: 75%). For FXM prediction, DSA C1q+ Ab was the most specific (95.8%, 85–100) and the combination of DSA-MFI > 2,300 and C1q+ Ab was the most sensitive (92.0%, 79.3–100). Conclusions. C1q+ Ab and LABScreen SAB DSA-MFI were significantly associated with FXM. DSA C1q+ Ab was highly specific but with low sensitivity.